2022
DOI: 10.1177/10870547221098181
|View full text |Cite
|
Sign up to set email alerts
|

Screen Time and ADHD Behaviors in Chinese Children: Findings From Longitudinal and Cross-Sectional Data

Abstract: Objective: Research suggests that screen exposure presents a risk for ADHD behaviors in young children. However, the operationalization of screen exposure remains murky and longitudinal data is scarce. In this paper, we examined the relations between better operationalized daily screen time and behaviors of inattention and behaviors of hyperactivity/impulsivity in three cohorts of community samples of young Chinese children. Method: Study 1 was longitudinal and included 111 children who were 3.6 years old (Ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Results from China, Canada and India reported a similar positive correlation between the two. 4,22,23 However, a study in the Netherlands showed no association between ST and ADHD, which is in contrast with the current findings. 24 The reason for no association between ST and ADHD could be that increased ST is associated with ADHD symptoms later in life in some children.…”
Section: Discussioncontrasting
confidence: 99%
“…Results from China, Canada and India reported a similar positive correlation between the two. 4,22,23 However, a study in the Netherlands showed no association between ST and ADHD, which is in contrast with the current findings. 24 The reason for no association between ST and ADHD could be that increased ST is associated with ADHD symptoms later in life in some children.…”
Section: Discussioncontrasting
confidence: 99%
“…The study shared that the time of watching television and using mobile phones had a risk of ADHD. A survey study from a longitudinal and cross-sectional in children (n = 596) [22] and a cross-sectional in young adults (n = 408) also con rmed this conclusion [23] that there was an association between early screen exposure and neurodevelopmental disorders. The previous study showed that individuals with ADHD began to be exposed to electronic screens earlier and for more extended periods, which easily affected their cognition development.…”
Section: Discussionmentioning
confidence: 83%
“…However, these studies focused on Euro-American children of primary school age, and the question of whether screen time affects Chinese preschool children’s approaches to learning during the pandemic received less attention. Tan and Zhou’s ( 2022 ) study, conducted in Chinese children, indicated that preschool children’s (aged 3 to 6) excessive screen time predicted children’s inattention problem, but they did not distinguish between the different types of screen time.…”
Section: Introductionmentioning
confidence: 99%